The Effect of Sociodemographic and Obstetric Characteristics of Pregnant Women on The Health of Newborn Babies: A Retrospective Study - Ebru Şahin; Gizem Deniz Büyüksoy (Çocuk Dergisi)
Objective: Birth history and obstetric characteristics of pregnant women are important factors which can determine the health of newborn babies. The aim of this study was to retrospectively examine the sociodemographic and obstetric characteristics of pregnant women and the health outcomes of newborns in deliveries performed in a hospital within a one year period. Materials and Methods: This study is retrospective, descriptive and correlational . The target population consisted of pregnant women who were both followed up and delivered in a private hospital in a city center between 1st January and 31st December , 2022. Sample selection was not made in the study, which included 440 pregnant women who were followed up between the specified dates. The data were collected using the patient information form prepared by the researchers, patient files, and patient registration forms in the hospital. The data were then analyzed using a computer. Results: The mean age was 29.47±4.64 years. All the pregnant women included in the study gave birth to live babies, and 53.9% of the babies were male. The mean birth weight was 3275.12±491.66 grams, and the mean height was 48.12±2.52 cm. The median Apgar score was 9 for the first minute of life. Age, pre-pregnancy weight, maternal weight at birth, reason for admission to hospital, delivery indications, number of abortions, number of multiple births and number of days in hospital were found to affect birth weight, height, head circumference and Apgar score in the first minute (p<0.05). Conclusion: As the weight of the pregnant women increases, the weight, height and head circumference of the babies increase, and the Apgar score is lower in pregnant women with repeated cesarean section indications. It is recommended that women’s health studies be planned both before and during pregnancy to improve neonatal growth and development indicators.